Sustained activation of PPARα by endogenous ligands increases hepatic fatty acid oxidation and prevents obesity in ob/ob mice - Huang, Jiansheng (Federation of American Societies for Experimental Biology, 2012)
Obesity, a major health concern, results from an imbalance between energy intake and expenditure. Leptin-deficient ob/ob mice are paradigmatic of obesity, resulting from excess energy intake and storage. Mice lacking acyl-CoA oxidase 1 (Acox1), the first enzyme of the peroxisomal fatty acid β-oxidation system, are characterized by increased energy expenditure and a lean body phenotype caused by sustained activation of peroxisome proliferator-activated receptor α (PPARα) by endogenous ligands in liver that remain unmetabolized in the absence of Acox1. We generated ob/ob mice deficient in Acox1 (Acox1(−/−)) to determine how the activation of PPARα by endogenous ligands might affect the obesity of ob/ob mice. In contrast to Acox1(−/−) (14.3±1.2 g at 6 mo) and the Acox1-deficient (ob/ob) double-mutant mice (23.8±4.6 g at 6 mo), the ob/ob mice are severely obese (54.3±3.2 g at 6 mo) and had significantly more (P<0.01) epididymal fat content. The resistance of Acox1(−/−)/ob/ob mice to obesity is due to increased PPARα-mediated up-regulation of genes involved in fatty acid oxidation in liver. Activation of PPARα in Acox1-deficient ob/ob mice also reduces serum glucose and insulin (P<0.05) and improves glucose tolerance and insulin sensitivity. Further, PPARα activation reduces hepatic steatosis and increases hepatocellular regenerative response in Acox1(−/−)/ob/ob mice at a more accelerated pace than in mice lacking only Acox1. However, Acox1(−/−)/ob/ob mice manifest hepatic endoplasmic reticulum (ER) stress and also develop hepatocellular carcinomas (8 of 8 mice) similar to those observed in Acox1(−/−) mice (10 of 10 mice), but unlike in ob/ob (0 of 14 mice) and OB/OB (0 of 6 mice) mice, suggesting that superimposed ER stress and PPARα activation contribute to carcinogenesis in a fatty liver. Finally, absence of Acox1 in ob/ob mice can impart resistance to high-fat diet (60% fat)-induced obesity, and their liver had significantly (P<0.01) more cell proliferation. These studies with Acox1(−/−)/ob/ob mice indicate that sustained activation of lipid-sensing nuclear receptor PPARα attenuates obesity and restores glucose homeostasis by ameliorating insulin resistance but increases the risk for liver cancer development, in part related to excess energy combustion.—Huang, J., Jia, Y., Fu, T., Viswakarma, N., Bai, L., Sambasiva Rao, M., Zhu, Y., Borensztajn, J., Reddy, J. K. Sustained activation of PPARα by endogenous ligands increases hepatic fatty acid oxidation and prevents obesity in ob/ob mice.